Barriers to Entry into Law School: An Examination of Socio-Economic and Indigenous Disadvantage - Angela Melville (Legal Education Review)
As law firms and law graduates work in an increasingly globalised environment and often work across multiple jurisdictions, this article outlines the results of a qualitative research project to assess employer perspectives on required graduate knowledge, skills and attributes. There is broad consensus among legal academics and practitioners that law schools need to deliver law programs that take cognisance of global developments and the increasing emphasis on internationalisation. This article addresses the question of how internationalisation is affecting what employers want from Australian law graduates and consequently what those law graduates need from their legal education both to secure jobs and to be as effective as possible as new employees, from the employers’ perspective. The findings presented in the article are based on a qualitative analysis of data gathered through representative employer roundtable discussions. Seven categories emerged, identifying the most important knowledge, skills and attributes required particularly for multi-jurisdictional practice. The findings provide a useful basis for law schools in their review, development and renewal of their law curriculum.